Terrorism in post-Soviet space. Comparative analysis of the phenomenon in the former Sovi-et republics after 2014 - Kaszuba, Malina; Stempień, Marta (Przegląd Wschodnioeuropejski, 2022)
The post-Soviet states are also known as the former Soviet Republics (FSR). With the collapse of the USSR in 1991, Moscow lost almost a quarter of its territory and nearly 150,000,000 people. As a result of this process, 15 sovereign states emerged or reemerged. The post-Soviet states are very diverse in terms of culture, economy, and politics. Moreover, the phenomenon of terrorism varies in the indicated area. The research goal of this study is to identify trends related to terrorism taking place in the post-Soviet space in the years 2014-2020 (in some cases, the analysis covers the years 2015-2019, due to data availability). The research area covers the former Soviet republics, which are further divided by the author into four subregions (Eastern Europe, Central Asia, Transcaucasia, and Baltic states) that are linked by cultural and geopolitical factors. Therefore, the research object covers 15 states and 4 subregions.